A Study on Hardfacing Alloy Using Fe-Cr and Fe-B Powders - Karip, E.; Aydin, S.; Muratoglu, M. (Polish Acad Sciences Inst Physics, 2015)
The aim of this study is the investigation of the effect of ferroboron and ferrochromium with massive wire based hardfacing alloys. Mixture of Fe-Cr and Fe-B powders was added to massive wire during welding process. Hardface layers were obtained by three different powder mixture and three different powder/massive wire proportions. Hardfacing was applied to two AISI 1020 steel substrates by open arc welding. Hardness test, scanning electron microscope and X-ray diffraction analysis were made to the samples. Test results showed that increasing ferroboron content and increasing powder mixture amount enhanced the microhardness of the specimens.
International Conference on Computational and Experimental Science and Engineering (ICCESEN) -- OCT 25-29, 2014 -- Antalya, TURKEY
Keywords: Surface-Properties; Wear Behavior; Cast Irons; Microstructure; Carbon; Boron